2023
DOI: 10.1177/15353702231177013
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network–based diagnostic models for lung cancer combining conventional indicators with tumor markers

Abstract: This study set out to establish a lung cancer diagnosis and prediction model uses conventional laboratory indicators combined with tumor markers, so as to help early screening and auxiliary diagnosis of lung cancer through a convenient, fast, and cheap way, and improve the early diagnosis rate of lung cancer. A total of 221 patients with lung cancer, 100 patients with benign pulmonary diseases, and 184 healthy subjects were retrospectively studied. General clinical data, the results of conventional laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Our results suggested that the nomogram model demonstrated high predictive accuracy, calibration, clinical applicability, and generalizability. At present, arti cial intelligence technology has demonstrated great potential and promising prospects, especially in the elds of lung cancer screening, imaging examination, pathological testing and biomarker detection [31] .Therefore, the potential of acoustic diagnosis for lung cancer remains largely unexplored. This study explores from the perspective of voice acoustic features for the rst time, combining it with clinical data and applying machine learning methods to construct models, laying the groundwork for intelligent diagnoses of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that the nomogram model demonstrated high predictive accuracy, calibration, clinical applicability, and generalizability. At present, arti cial intelligence technology has demonstrated great potential and promising prospects, especially in the elds of lung cancer screening, imaging examination, pathological testing and biomarker detection [31] .Therefore, the potential of acoustic diagnosis for lung cancer remains largely unexplored. This study explores from the perspective of voice acoustic features for the rst time, combining it with clinical data and applying machine learning methods to construct models, laying the groundwork for intelligent diagnoses of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that ML algorithms are more advantageous than traditional statistical methods when constructing predictive models. Artificial neural networks are capable of self-learning, adaptation, fault-tolerance, nonlinearity, and efficient mapping of inputs to outputs [ 25 , 26 ], and have been used effectively to differentiate between mild cognitive impairment and Alzheimer's disease, to develop predictive models for lung cancer diagnosis, and for risk prediction of cardiovascular disease [ [27] , [28] , [29] ]. Decision trees are useful for determining groupings, recognizing connections between groups, and forecasting upcoming occurrences [ 30 ].…”
Section: Introductionmentioning
confidence: 99%